Melatonin immersion improves postharvest quality and antioxidant capacity of ‘Nam Dok Mai’ mangoes during storage at ambient temperature - P. Boonyaritthongchai; Punika Sangsuk; Suriyan Supapvanich; Chalermchai Wongs-Aree; Nutthachai Pongprasert; Janejira Phakawan (Agriculture and Natural Resources, 2025)
Importance of the work: Quality loss and delays in ripening in mangoes were explored based on melatonin (MT) immersion as a natural, effective postharvest treatment under ambient conditions. Objectives: To evaluate MT efficacy in preserving the quality, delaying ripening and enhancing oxidative stress resistance in mangoes under ambient storage. Materials and Methods: The mangoes were immersed in water (control) or in a solution of 0.5 mM MT for 1 hr and thereafter stored at room temperature for 10 days. Results: Mangoes treated with 0.5 mM MT had nearly 17% and 60% lower respiration rates and ethylene production, respectively, than untreated ones at the climacteric peak during storage, contributing to a slower ripening process and delayed progression of both peel and pulp coloration. In terms of internal quality, MT application effectively slowed the decline in firmness, suppressed the rise in the total soluble solids-to-titratable acidity ratio. In addition, the MT-treated fruits had enhanced antioxidant defense, as shown by elevated activities of superoxide dismutase, catalase and ascorbate peroxidase. These responses were accompanied by significantly lower levels of hydrogen peroxide, malondialdehyde and lipoxygenase activity, suggesting reduced oxidative membrane damage. Collectively, these findings demonstrated that MT immersion contributed to better quality preservation and improved resistance to postharvest deterioration and disease through modulation of oxidative stress and antioxidant metabolism. Main finding: Subjecting mangoes to postharvest MT treatment was a feasible approach to preserve their postharvest quality and to stimulate antioxidant capability.
Keywords: Postharvest Quality and Shelf Life Management; Plant Physiology and Cultivation Studies; Phytochemicals and Antioxidant Activities